Dieting for an emperor : a translation of books 1 and 4 of Oribasius' Medical compilations with an introduction and commentary - Oribasius. (Studies in Ancient Medicine, 1997)
The commentary indicates Oribasius' source for each quotation or paraphrase, assesses the accuracy and comprehensibility of the contents, and suggests the reasons behind the recommendations and rejections of certain cakes, breads, fruits and vegetables. To aid further research in the field of ancient dietetics, a detailed word index is appended. The introduction summarises the more important points about the medical theories behind the humours and qualities, and how regulating the intake of foods could assist in the maintenance of good health.